( a 5 + b 5 + c 5 ) 2 ( a 3 + b 3 + c 3 ) 2 ( a 4 + b 4 + c 4 ) Let a , b and c be non-zero real numbers such that a + b + c = 0 . The value of the above expression can be represented by n m , both coprime positive integers. Calculate the value of m + n .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Did the same way.
Did the same way.
The problem allows substituting any three non-zero real values for a , b and c as long as a + b + c = 0 and the denominator is non-zero.
Let a = 2 and b = c = − 1 .
Substituting gives:
( 3 2 − 1 − 1 ) 2 ( 8 − 1 − 1 ) 2 ⋅ ( 1 6 + 1 + 1 ) =
3 0 2 6 2 ⋅ 1 8 = 5 2 1 8 = 2 5 1 8 = n m
So m + n = 1 8 + 2 5 = 4 3 .
I did it in a same way.
I Also did in the same way and even used the same values of a,b,c ! :)
Nice solution
Nice solution! :)
Nice solution
By the statement we have a+b+c=0. Then, we have :
replacing the expression
I used Newton sum here.
First finding ( a 3 + b 3 + c 3 ) .
a
3
+
b
3
+
c
3
=
(
a
+
b
+
c
)
(
a
2
+
b
2
+
c
2
)
−
(
a
b
−
b
c
−
c
a
)
(
a
+
b
+
c
)
+
3
a
b
c
a
3
+
b
3
+
c
3
=
3
a
b
c
⇒
(
a
3
+
b
3
+
c
3
)
2
=
9
(
a
b
c
)
2
Second finding ( a 4 + b 4 + c 4 ) .
a
4
+
b
4
+
c
4
=
(
a
2
+
b
2
+
c
2
)
2
−
2
[
(
a
b
)
2
+
(
b
c
)
2
+
(
c
a
)
2
]
a
4
+
b
4
+
c
4
=
[
(
a
+
b
+
c
)
2
−
2
(
a
b
+
b
c
+
c
a
)
]
−
2
[
(
a
b
)
2
+
(
b
c
)
2
+
(
c
a
)
2
]
⇒
a
4
+
b
4
+
c
4
=
2
[
(
a
b
)
2
+
(
b
c
)
2
+
(
c
a
)
2
]
Third finding ( a 5 + b 5 + c 5 ) .
a
5
+
b
5
+
c
5
=
(
a
+
b
+
c
)
(
a
4
+
b
4
+
c
4
)
−
(
a
b
+
b
c
+
c
a
)
(
a
3
+
b
3
+
c
3
)
+
a
b
c
(
a
2
+
b
2
+
c
2
)
a
5
+
b
5
+
c
5
=
(
a
b
+
b
c
+
c
a
)
(
−
5
a
b
c
)
⇒
(
a
5
+
b
5
+
c
5
)
2
=
(
a
b
+
b
c
+
c
a
)
2
(
−
5
a
b
c
)
2
=
[
(
a
b
)
2
+
(
b
c
)
2
+
(
c
a
)
2
]
(
−
5
a
b
c
)
2
⇒ ( a 5 + b 5 + c 5 ) 2 ( a 3 + b 3 + c 3 ) 2 ( a 4 + b 4 + c 4 )
⇒ [ ( a b ) 2 + ( b c ) 2 + ( c a ) 2 ] × 2 5 ( a b c ) 2 9 ( a b c ) 2 × 2 [ ( a b ) 2 + ( b c ) 2 + ( c a ) 2 ]
⇒ 2 5 1 8 = n m
⇒ m + n = 1 8 + 2 5 = 4 3
Problem Loading...
Note Loading...
Set Loading...
We can use Newton's sums method to solve this problem. Let P n = a n + b n + c n , S 1 = a + b + c = P 1 = 0 , S 2 = a b + b c + c a and S 3 = a b c . Then, we have:
\(\begin{array} {} P_2 = a^2+b^2+c^2 = S_1P_1 -2S_2 = 0 - 2S_2 & = -2S_2 \\ P_3 = a^3+b^3+c^3 = S_1P_2 -S_2P_1 + 3S_3 = 0 - 0 + 3S_3 & = 3S_3 \\ P_4 = a^4+b^4+c^4 = S_1P_3 -S_2P_2 + S_3P_1 = 0 - S_2(-2S_2) + 0 & = 2S_2^2 \\ P_5 = a^5+b^5+c^5 = S_1P_4 -S_2P_3 + S_3P_2 = 0 - S_2(3S_3) + S_3(-2S_2) & = -5S_2S_3 \end{array} \)
⇒ ( a 5 + b 5 + c 5 ) ( a 3 + b 3 + c 3 ) 2 ( a 4 + b 4 + c 4 ) = P 5 2 P 3 2 P 4 = ( − 5 S 2 S 3 ) 2 ( 3 S 3 ) 2 ( 2 S 2 2 ) = 2 5 1 8
⇒ m + n = 1 8 + 2 5 = 4 3